Vozdushnye puti records
Correspondence, writings, editorial records, clippings, printed matter, annotated sheet music, photographs, negatives, and other records of Vozdushnye Puti (Aerial Ways), a journal of Russian literary criticism.
Collection material in Russian, with English, French, and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Vozdushnye puti; Criticism; Russian literature; Russian literature -- History and criticism